Synthesis gas production of municipal solid waste in a fluidized bed gasifier using thermodynamic equilibrium model - Nur Ashikin, Jamin; Noor Asma Fazli, Abdul Samad; Suriyati, Saleh (Universiti Malaysia Pahang, 2018)
In this paper, the thermodynamic equilibrium model has been developed to predict the compositions of MSW producer gases in fluidized bed gasifier. Two main compositions of MSW were selected to represent the model namely food and wood waste. The objectives of this work are to study the effect of gasification temperature on the amount syngas produced and gasification performance in terms of synthesis gas yield, lower heating value (LHV), cold gas efficiency and carbon conversion of feedstock. Based on the simulation of thermodynamic equilibrium model using food waste as feedstock, the results obtained show the amount of hydrogen (H2) and carbon monoxide (CO) gas production are increased linearly from 29.58 to 34.03% and 31.85 to 45.78% respectively as the gasification temperature is increased from 650 to 1000 °C. In contrast, the amount of carbon dioxide (CO2) and methane (CH4) gas produced are decreased from 33.26 to 19.17% and 5.31 to 1.02% respectively. In addition, gasification of wood waste also shows similar behavior as the H2 and CO gas are increased proportionally to the gasification temperature from 31.25 to 39.87% and 26.33 to 34.81% respectively. The production of CO2 and CH4 gas also shows it decrement from 38.75 to 23.38% and 3.67 to 1.94%. Meanwhile, food waste and wood waste gasification also shows the same trend in terms of increment of synthesis gas yield, lower heating value (LHV), cold gas efficiency and carbon conversion. As the gasification temperature is increased from 650 to 1000 °C, the synthesis gas yield are increased for both food waste and wood waste from 1.22 to 1.61 Nm3/kg and 1.36 to 1.85 Nm3/kg respectively. The LHV of the food waste and wood waste also increases consistently with gasification temperature from 4.56 to 5.00 MJ/ Nm3 and 5.60 to 6.57 MJ/ Nm3 respectively. CGE is increased from 31.9372 to 46.03 and 39.66 to 63.19% for food waste and wood waste respectively as the gasification temperature increased. The carbon conversion percentage increase corresponds to the gasification temperature from 48.69 to 59.88% and 57.26 to 68.08% for food waste and wood waste respectively.